Expressive Speech Acts in the Introductory Discourse of Online Dating Tinder in Malaysia - Sya’adah, Himatus; Joko Prayitno, Harun; Sabardila, Atiqa; Purnomo, Eko (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Tinder is a popular social media platform that is widely used in Malaysia. This research aims to describe the form of expressive speech acts in the introductory discourse of the online dating media Tinder in Malaysia. This type of research employed a qualitative descriptive technique. The data used consists of words or phrases with expressive speech acts. The data source for this research is chats used by netizens on the online dating application Tinder in Malaysia. The research's method of collecting data involved listening, taking notes, and documenting. The data analysis method used in this research is the intralingual and extra-lingual matching method. The findings indicated that numerous expressive speech acts were included in the Tinder introduction application used in Malaysia. Expressive speech acts are speech acts that function to express or show the speaker's psychological attitude towards a situation, such as congratulating, apologizing, thanking, blaming, praising, blaming, forgiving, and condoling The expressive speech acts found were 33% of the expressive speech acts of praise, 21% of the expressive speech acts of congratulations or greetings, 12% of the expressive speech acts of apologizing, 12% of the expressive speech acts of praying, and 13% of the expressive speech acts of admiration. The frequency of expressive speech acts of praising is 33%, whereas that of apologizing is 12%. The results showed that the form of praise is the most dominant expressive speech act. Therefore, it can be concluded that speakers in Tinder media use expressions of praise to attract interest in interlocutors and engage in conversation.